Integrasi Neurosains dan Nilai-Nilai Islam Dalam Strategi Pembelajaran: Kajian Tentang Otak, Pendidikan dan Belajar - Ihsan; Ahmad Lahmi; Dasrizal Dahlan; Rosniati Hakim (Suria Academic Press, 2025)
Advances in neuroscience have opened new horizons in the field of education, particularly in understanding how the brain functions in the learning process. This article examines the integration of neuroscientific findings and Islamic educational values in designing effective, adaptive, and holistic learning strategies. Using a qualitative literature review approach, the study explores concepts of brain function, the principles of neuroplasticity, and the role of emotions in learning, and relates them to Islamic perspectives on intellect (ʿaql), spirit (rūḥ), and the formation of the insān kāmil (the complete human being). The findings indicate that the learning process is strongly influenced by brain structure and function, including the involvement of emotions and meaningful experiences. Islamic education, through its concepts of intellect and heart (qalb), aligns with neuroscientific approaches in shaping learning systems based on compassion, personalization, and spirituality. Therefore, teachers and Islamic educational institutions need to understand the basic principles of neuroscience in order to create adaptive learning experiences that are spiritually meaningful.